Snapshots in obstetrics & gynecology - Saxena, Richa (Japee Brothers Medical Publishers, 2012)
This book "Snapshots in Obstetrics and Gynecology" aims at simplifying the subject of obstetrics and gynecology as much as possible. The idea behind "snapshots" is to present all important topics in obstetrics and gynecology, which are encountered in the clinical practice in form of brief snippets and snapshots. The book has been broadly divided into two sections-obstetrics and gynecology. The section on obstetrics has 5 Chapters, while the section on gynecology has 10 Chapters.